User Experience of Mobile Phone Users in Exploring and Reading Nonfiction Books - Andries, Fivy A.; Posumah, Jenie (Journal of English Culture, Language, Literature and Education, 2023)
The use of mobile phones should be able to make a positive contribution to its users while increasing reading habits We believe that it is very important for users to find information on several non fiction books related to their needs and desires as well as developing a high potential platform business model This paper aims to map the relationship between user experience in exploring and reading nonfiction books using mobile phones The study is a human center and a qualitative approach which will carry out an analysis of the surveys distributed and user experience obtained from the interview results Based on the data obtained not everyone uses mobile phones to read nonfiction because there are those who rarely read nonfiction using mobile phones and prefer to use books but based on their experience reading nonfiction via mobile phones is very helpful and practical The internet is also a supporting factor in nonfiction browsers via mobile phones < p>